2009
DOI: 10.3109/01902140902918755
|View full text |Cite
|
Sign up to set email alerts
|

The Macrolide Clarithromycin Inhibits Experimental Post-Transplant Bronchiolitis Obliterans

Abstract: Chronic allograft dysfunction in form of bronchiolitis obliterans is the most important hurdle to improved longterm survival after clinical lung transplantation to date. Recently, it was observed that the progression of bronchiolitis obliterans in lung transplant recipients might be inhibited by macrolide antibiotics. The authors therefore tested whether macrolide therapy can attenuate fibrous obliteration of airways in an animal model of bronchiolitis obliterans. Rats with heterotopic tracheal allografts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There has been one published study on the role of clarithromycin in the treatment of BOS after lung transplantation, which was equally effective as azithromycin [23]. Moreover, also in a tracheal transplant model, clarithromycin was able to inhibit experimental post-transplant obliterative bronchiolitis in rats [24]. In this study, rats were treated intraperitoneally with clarithromycin.…”
Section: Discussionmentioning
confidence: 95%
“…There has been one published study on the role of clarithromycin in the treatment of BOS after lung transplantation, which was equally effective as azithromycin [23]. Moreover, also in a tracheal transplant model, clarithromycin was able to inhibit experimental post-transplant obliterative bronchiolitis in rats [24]. In this study, rats were treated intraperitoneally with clarithromycin.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study on the rat model of heterotopic tracheal allotransplantation, Remund et al. (25) demonstrated that the macrolide antibiotic clarithromycin can significantly prevent tracheal fibro‐obliteration by down‐modulating TNF‐α and γ‐IFN production. Increased levels of IL‐8 and other pro‐inflammatory mediators in BAL, as well as neutrophilia, have been observed in some LTRs with established or future BOS, and some of these features have been shown to pre‐date BOS onset (8–13, 30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…BOS may be classified into fibroproliferative and neutrophilic, the latter responding to AZM, the former being refractory [259][260][261][262][263][264]. In these patients, macrolides have presented beneficial results in improving respiratory capacity [245,246]. Shirit et al [250] did not demonstrate improvement in respiratory capacity.…”
Section: Macrolides and Bronchiolitismentioning
confidence: 94%
“…Bronchiolitis obliterans syndrome (BOS) is the leading cause of death in lung transplant recipients. It has recently been noted that the progression of BOS in lung-transplant recipients might be inhibited by macrolides [245][246][247][248][249][250][251][252][253][254][255][256][257][258]. BOS may be classified into fibroproliferative and neutrophilic, the latter responding to AZM, the former being refractory [259][260][261][262][263][264].…”
Section: Macrolides and Bronchiolitismentioning
confidence: 99%